2018
DOI: 10.2169/internalmedicine.0531-17
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Reinfection by <i>Nocardia</i> in an Immunocompetent Patient with Bronchiectasis

Abstract: Pulmonary reinfection by Nocardia has been rarely reported. We describe a case of pulmonary reinfection by Nocardia in an immunocompetent patient. An 82-year-old immunocompetent woman with bronchiectasis presented with exacerbation of cough. She had a history of pulmonary nocardiosis three years earlier. At that time, Nocardia species were cultured from the sputum and identified as N. cyriacigeorgica with 16S ribosomal RNA gene sequencing. In the present episode, cultures of sputum and bronchial washing specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Additionally, these isolates showed varying susceptibilities to different antibiotics. Different Nocardia species may have different susceptibility profiles, and this information is crucial for providing adequate antimicrobial therapy as well as investigating the epidemiology of Nocardia infections (Tamakoshi et al, 2018). When Nocardia is isolated from clinical specimens, the species should be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, these isolates showed varying susceptibilities to different antibiotics. Different Nocardia species may have different susceptibility profiles, and this information is crucial for providing adequate antimicrobial therapy as well as investigating the epidemiology of Nocardia infections (Tamakoshi et al, 2018). When Nocardia is isolated from clinical specimens, the species should be identified.…”
Section: Discussionmentioning
confidence: 99%
“…PN occurred in COPD and bronchiectasis patients without any other immunosuppressive factors. 12 PN in bronchiectasis or COPD might be related to the decrease of airway clearance and the local pulmonary immune function which leads to an increased chance of Nocardia colonization in the lower respiratory tract. 13 Patients with COPD and asthma need to inhale glucocorticoids frequently, and even use systemic glucocorticoids for a short time during acute attacks, which might increase the risk of PN.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] Nevertheless, antimicrobial susceptibility tests are essential since they may differ among Nocardia species. [ 16 , 17 ] In addition, some authors suggested that brain imaging should be considered in all patients with pulmonary nocardiosis. [ 2 ] Regarding the tools for species identification, 16S ribosomal RNA gene PCR is recommended as a feasible method since the test is rapid, inexpensive, and reliable.…”
Section: Discussionmentioning
confidence: 99%